Cannabis Allergy: Medical Use in the Context of Contemporary Issues and Risks - Lisiecka, Maria Zofia (Gaceta Médica de Caracas, 2024)
Legalizing cannabis will increase its use in both recreational and medical contexts, leading to a rise in allergic reactions. Research in this field will help uncover potential risks and provide crucial information to the medical community for improving usage and minimizing adverse outcomes. Objective: This article aimed to provide a comprehensive overview of allergic reactions to cannabis and evaluate its impact on health and society. Method: This research employed an analytic-synthetic approach. The necessary information for the article was obtained and analyzed from electronic scholarly sources. Results: As a result of this study, it was identified that healthcare professionals’ knowledge regarding the application of cannabis and its compounds in clinical practice is limited, thereby lacking experience in treating cannabis allergies. Active education of medical practitioners regarding the application of cannabinoids and potential allergic reactions is necessary, especially as cannabis consumption continues to rise.